Social isolation and stress related hormones modulate the stimulating effect of ethanol in preweanling rats - Arias Grandio, Carlos (2010)
Preweanling rats are highly sensitive to the locomotor stimulation induced by relatively high ethanol doses. In adult mice this ethanol effect is modulated by stress. The goal of the present study was to analyze the role of stress and corticosterone in the stimulating effect of ethanol in preweanling rats. In Experiment 1 15-day-old rats were separated from the mother during a period of 4 h in which subjects remained isolated or paired with a littermate. In a third condition pups remained in the home-cage with the dam. After this isolation period pups were given ethanol (0 or 2.5 g/kg) and were tested in a novel environment. Previous data have shown that a similar period of isolation is enough to increase corticosterone levels in preweanling rats. Experiment 2 evaluated the effect of exogenous administration of corticosterone (0, 3 or 6 mg/kg) along with ethanol, and Experiment 3 tested ethanol-mediated locomotor activation in adrenalectomized preweanling rats. The last experiment aimed to test the role of corticotropic releasing factor 1 (CRF1) receptors in locomotion induced by ethanol in isolated pups. According to our results there is a synergism between stress or corticosterone and ethanol in preweanling rats. The interaction between stress (induced by social isolation) and ethanol seems to be mediated by CRF, since blockade of CRF1 receptors cancelled the effect of ethanol in isolated pups. This study highlights the importance of considering stress as a possible intervening variable in studies evaluating ethanol effects in developing animals when maternal separation is used in the experimental procedure.